Urinalysis in primary care doctor practice - Bartlomiej Szewczyk; Kamila Szewczyk; Paulina Pytel; Wiktoria Julia Krzesłowska; Weronika Hołownia; Szymon Wiśniewski (Journal of Education, Health and Sport, 2024)
Introduction: